PEREBEDAAN KETAHANAN FISIK PADA ANAK SEKOLAH DASAR STUNTING DAN TIDAK STUNTING DI KOTA KUPANG - putu amrytha sanjiwani (CHMK HEALTH JOURNAL, 2019)
School age children is young generation who will continue sustainable development of this country. They are in very fast and active growth period. Malnutrition suffer in this period will give negative effect for children like weakness, decrease child’s cognition and influence their physical endurance. Aim of this study is to analyse differentiation of physical fitness between stunting and non stunting elementary school children in Kupang city. This study use Simple Random Sampling method and contribute 208 4th level of school age children in Kupang city. They divided into 2 groups which are stunting and non-stunting group. This study found more than 70% of respondents have average and above physical fitness. Based on Mann U Whitney test, this study found children who belong to stunting group have fitness index lower than non-stunting children even though not significant different (p=0.137) Keywords: Physical fitness, stunting, physical endurance